Improving students’ speaking skill through cooperative learning model role-playing in primary students - Siddik, Mohammad (Opción, 2019)
The objective of the research was to apprehend the improvement of students’ skill ability through the implementation of cooperative learning role-playing with the aid of descriptive design method. This research was conducted in different cycles such as planning, treatment, observation, and reflection; each cycle was conducted in two meetings. Furthermore, a test was given to the students in every cycle at the end of each meeting. This test was aimed at monitoring the results of their learning. The results of the data analysis show a significant improvement in students’ speaking in the lesson of the simple interview in every cycle.